Assessment of error levels across the domain of a three dimensional underwater motion capture methodology - Thompson, I. M.; Banks, J.; Warner, M.; Hudson, D. (ISBS Proceedings Archive (Michigan), 2022)
Assessing human movement underwater presents many challenges, and it is therefore important to understand error across the whole capture domain to ensure accuracy in resulting kinematics. This study assessed the accuracy across the capture domain of a submerged motion capture methodology. Six Qualisys cameras created an underwater capture volume of 8x2x2m. Average error levels across the domain were acceptable in two uncertainty trials (1.23mm ± 8.23mm and 1.34mm ± 9.65mm), but error increased at the ends and top of the domain. By selecting an area of interest for assessment that excluded areas with lower accuracy, error was reduced to 0.53mm (± 1.45mm). This study highlights the need to investigate error levels across a motion capture domain, particularly when this is a large volume, to ensure results obtained from investigations are reliable.